Ketahanmalangan Pengelola PKBM Dalam Mengembangkan Inovasi Pendidikan Nonformal - Devi Merina Tuz Sa’diyah; Ahmad Ahmad; Nilna Sa’adayah (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
The focus of this research is to describe the strategy of adversity quotient for the management of the Community Learning Activity Center (PKBM) to develop innovations in turning barriers into opportunities for non-formal education programs. Qualitative research with this type of case study was carried out at PKBM Mentari, using structured interviews as the primary data collection method, in order to obtain primary data and document matrix methods to obtain secondary data. the data were analyzed using interactive techniques belonging to Miles and Huberman with the stages of data reduction, data presentation and conclusion drawing. The results of this study are the adversity quotient strategy that generally implemented by PKBM is very good, this can be seen from the indicators including: 1) Organizing learning activities flexibly in terms of time, so that it does not interfere with the daily activities of the community; 2) Provide learning at affordable costs so as not to burden the community in participating in learning; 3) Making the community the main partner in the continuation of teaching and learning activities at PKBM and 4) Building synergies with local village officials. The relatively short research time is the main limitation in compiling this study, so that it only maximizes the statements of the main informants.